2021
DOI: 10.48550/arxiv.2108.01992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Search on Johnson Graphs by Continuous-Time Quantum Walk

Hajime Tanaka,
Mohamed Sabri,
Renato Portugal

Abstract: Spatial search on graphs is one of the most important algorithmic applications of quantum walks. To show that a quantum-walk-based search is more efficient than a random-walk-based search is a difficult problem, which has been addressed in several ways. Usually, graph symmetries aid in the calculation of the algorithm's computational complexity, and Johnson graphs are an interesting class regarding symmetries because they are regular, Hamiltonconnected, vertex-and distance-transitive. In this work, we show tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…For later use, we first recall the subspace of the Hilbert space H V = span v : v ∈ V used in the spatial search by continuous-time QW [18]. Consider the following subsets of V:…”
Section: The Spatial Search Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…For later use, we first recall the subspace of the Hilbert space H V = span v : v ∈ V used in the spatial search by continuous-time QW [18]. Consider the following subsets of V:…”
Section: The Spatial Search Algorithmmentioning
confidence: 99%
“…As in [18], we invoke the implicit function theorem for complex analytic functions [23]. Extend for the moment the range of ǫ to complex numbers with |ǫ| 2 < (2k − 1) −1 , so that the functions p ℓ (ǫ) and e ± ℓ (ǫ) are all analytic.…”
Section: An Eigenbasis Of the Invariant Subspacementioning
confidence: 99%
See 1 more Smart Citation
“…For distance regular graphs with larger diameter, Wong [17] and then Tanaka et al [15] proved that the Johnson graphs J(n, k), for constant k ≥ 3, have spatial search. Since the constant spectral gap condition holds for Johnson graphs, this provides an alternative and immediate proof that they have optimal spatial search.…”
Section: Introductionmentioning
confidence: 99%
“…While this idea was formalized by Shenvi, Kempe and Whaley [14], its first application dates back to 1996, when Grover [11] showed that finding a marked vertex in a looped K n takes O( √ n) steps of a quantum walk. Since then, quantum walk search has been studied on various graphs, including hypercubes [14], Cartesian powers of cycles [6], strongly regular graphs [13], certain Johnson graphs [2,19,20,16], and more generally, regular locally arc-transitive graphs [12]. For most of these graphs, quantum walks arrive at the marked vertices faster than the classical random walks.…”
Section: Introductionmentioning
confidence: 99%